Presentation of this thematic issue (Quinto Sol, 2013)
All contributions in this issue refer to indigenous peoples in Argentina. In this presentation, Mirta Zink and Claudia Salomón Tarquini, in charge of editing this issue in all its sections, make a series of considerations about the origin of the texts and their features.
Keywords: indigenous peoples; history; anthropology